pH-dependent fouling mechanisms of polyamide Janus membrane during membrane distillation treatment of landfill leachate - Binbin Li; Zhongsen Yan; Yuandong Lin; Haiqing Chang; Yuting Lin; Huiyi Cai; Fangshu Qu (Journal of Environmental Chemical Engineering, 2026)

Mechanistic insights into the long-term stabilization of Cr(VI) by modified nanoscale zero-valent iron in sediments - Yiqun Xu; Jie Dai; Leixin Huang; Weilong Lin; Yunlong Zhu; Xiaoding Huang; Rongzhong Wang; Binbin Shao; Wenjing Xue (Journal of Contaminant Hydrology, 2026)

Green synthesis of N-doped hierarchical porous biochar from Artemisia leaf for enhanced peroxydisulfate activation: Synergistic roles of edge nitrogen and carbonyl group - Lin Ge; Zhan Chen; Yuan Pan; Xiansheng Zhang; Teng Li; Xinyi Huang; Binbin Shao; Sheng Liu; Yunze Wang; Yu Zhang; Zhifeng Liu (Environmental Research, 2026)

Tailoring the enzymatic microenvironment in bifunctional macroporous resins: Synergizing interfacial activation and structural rigidity for process-intensified biocatalysis in extreme solvents - Qingqing Liu; Jiaxiang Du; Weihang Lin; Xuanling Zhang; Yi Hu; Binbin Nian (Chemical Engineering Journal, 2026)

Janus composite membranes for suppressing thermal wetting in membrane distillation of flue gas desulfurization wastewater - Xinxin Lin; Qiaoling Ye; Binbin Li; Huiyi Cai; Caiyi Fan; Zhongsen Yan (Journal of Water Process Engineering, 2026)

Robust burst bubble recognition in flotation froths via RGB-D imaging and depth-guided feature extraction - Lin Zhao; Zebin Zou; Binbin Dong; Lang Liu; Yongfang Xie; Shiwen Xie (Minerals Engineering, 2026)

Thunderstorm activity over Fujian and Vicinity: Insights from thunderstorm tracking technology - Biao Zhu; Binbin Lin; Tingting Chen; Dan Li; Bo Pang; Hengyi Liu (Journal of Atmospheric and Solar-Terrestrial Physics, 2026)

Catalytic co-pyrolysis of sewage sludge and corn stover over self-sourced activated biochar: Product distribution, nitrogen migration, and heavy metal immobilization - Xiaojie Zhuansun; Binbin Tang; Zhen Sun; Hongtao Li; Peng Fu; Xiaona Lin (Fuel, 2026)

Identification of Closantel as a small-molecule inhibitor of the compact CRISPR-Cas RNA editor Cas13bt3 - Xulong Chen; Binbin Zhan; Ruyi Shi; Jingxuan Chen; Zhonghui Lin; Zuoan Li (Molecular Diversity, 2026)

Deficiency of TEX264-mediated reticulophagy is linked to ER stress-induced neuronal necroptosis: Implication of fluoride-associated hippocampal injury and cognitive dysfunction - Ge Du; Quan Yuan; Rui Liu; Jiaming Liang; Milan Yang; Yufei Gao; Xiaoli Liu; Siman Lin; Rui Zhang; Binbin Wang; Dongmei Wang; Hua Fan (Journal of Environmental Sciences, 2026)

Achieving “one stone, three birds”: A solid-waste steel-slag-derived system for synergistic antibiotic degradation and CO2 capture - Shiping Zhang; Xiaoyong Wu; Baolin Zhao; Gui Yang; Shenxu Bao; Xueying Chen; Ling Xia; Yao Wang; Juan Long; Yang Wu; Lin Wang; Binbin He (Journal of Cleaner Production, 2026)

Endoscopic prediction model for detecting advanced rectal polyps after ileorectal anastomosis in familial adenomatous polyposis: a dual-center retrospective study - Zhilin Liu; Xingjie Gao; Shuling Chen; Linfu Zheng; Binbin Xu; Gaozhen Deng; Wen Wang; Kun Lin; Chushu Li; Zhou Ye; Dazhou Li (Familial Cancer, 2026)

Endoplasmic reticulum stress-induced CHOP activation mediates NLRP3 inflammasome-dependent pyroptosis in BDE-47-induced cognitive dysfunction - Quan Yuan; Rui Zhang; Jun Hu; Siman Lin; Ying Zhu; Junhong Geng; Ge Du; Xiao Yang; Yipin Zhao; Dongmei Wang; Binbin Wang; Hua Fan (NeuroToxicology, 2026)

Study on Single-Point Mooring Cables for Stereoscopic Environmental Monitoring in the Natural Gas Hydrate Area of the South China Sea - Yifei Dong; Shuangling Dai; Qianyong Liang; Jiawang Chen; Haojie Si; Binbin Guo; Andi Xu; Dongqing Ma; Zhigang Wang; Danyi Su; Xuemin Wu; Yan Sheng; et al. (Journal of Marine Science and Engineering, 2026)
Safe exploitation of the marine natural gas hydrate (NGH) resource is essential to meet the demand of the future energy requirement. To enable real-time monitoring of methane leakage during the production test of NGH, an ocean stereoscopic monitoring system based on underwater single-point mooring structure is developed, which supports in situ monitoring of marine environment at the sea-air interface, the euphotic zone, and the seabed boundary layer. Numerical simulations were conducted to evaluate the effect of mooring configuration, cable lengths, and buoyancy settings on the mooring stability of the system against the current and waves. Based on the simulation result, an optimized segmented inverse-catenary mooring configuration is developed to achieve a balance between the performance and cost. The designed submersible relay buoy isolates the upper dynamic S-shaped cable from the lower static straight electro-optical-mechanical (EOM) cable, thereby improving system stability. The monitoring system based on the optimized mooring structure is successfully deployed at the NGH zone in the northern South China Sea at the water depth of 1330 m confirming its working stability in harsh sea conditions.

Engineering local donor-acceptor architecture in a porphyrin-based metal-organic framework for enhanced sonocatalytic immunotherapy - Yarui Hu; Sainan Liu; Jiwei Wang; Zhendong Liu; Xinyu Ma; Junhao Shao; Binbin Ding; Ping'an Ma; Jun Lin (Chemical Engineering Journal, 2026)

Microbial processing of organic matter in cold seep sediments revealed by amino compound distributions and degradation indices - Yang Wu; Lina Lyu; Meiqing Lin; Shengtao Ma; Cheng Yang; Rong Wu; Kaiqin Huang; Xi Xiao; Yifei Dong; Binbin Guo; Danyi Su; Jing Zhao; et al. (Marine Pollution Bulletin, 2026)

Optimizing light and nitrogen distribution in maize-soybean intercropping systems to enhance crop yield - Zhen Fan; Binbin Qiang; Xinbo Zhang; Yanrong Lin; Yulin Wu; Xining Zhao; Enke Liu; Tie Cai; Peng Zhang; Tiening Liu; Xiaolong Ren; Xiaoli Chen (European Journal of Agronomy, 2026)

Leaf senescence and source-sink dynamics in soybean: Insights from maize-soybean intercropping systems - Zhen Fan; Binbin Qiang; Yanrong Lin; Pengzhao Liu; Zhipeng Li; Mengwei Cheng; Xining Zhao; Xiaolong Ren; Xiaoli Chen (Field Crops Research, 2025)

Eukaryotic expression and characterization of two α1,2-fucosyltransferase genes in the histo-blood group antigens synthesis pathway of the Pacific oyster (Crassostrea gigas) - Junxia Hu; Meng Qu; Weiran Zhang; Binbin Gui; Yanhua Jiang; Lin Yao; Shixin Wang; Dapeng Wang (Glycoconjugate Journal, 2025)

Combined non-volatile and volatile metabolite profiles and antioxidant activities reveal the enhancement of traditional “steaming and Sun-drying nine times” on the functional properties of jujube - Yu Liu; Lijuan Zhang; Haijiao Lin; Zengyi Song; Pu Xu; Liming Zhang; Binbin Wei (Food Chemistry, 2025)

Hyperlocal disaster damage assessment using bi-temporal street-view imagery and pre-trained vision models - Yifan Yang; Lei Zou; Bing Zhou; Daoyang Li; Binbin Lin; Joynal Abedin; Mingzheng Yang (Computers, Environment and Urban Systems, 2025)

Root plasticity improves the potential of maize/soybean intercropping to stabilize the yield - Zhen Fan; Pengzhao Liu; Yanrong Lin; Binbin Qiang; Zhipeng Li; Mengwei Cheng; Qihang Guo; Jinpeng Liu; Xiaolong Ren; Xining Zhao; Xiaoli Chen (Soil and Tillage Research, 2025)

Global marine methane seepage: Spatiotemporal patterns and ocean current control - Xin Ni; Xiuguo Liu; Shilong Pang; Yifei Dong; Binbin Guo; Yuhang Zhang; Yang Wu; Danyi Su; Andi Xu; Qingmeng Yuan; Xuemin Wu; Lin Yang; et al. (Marine Geology, 2025)

Analysis of temporal and spatial distribution of CG lightning activity and its relationship with terrain features around Jiuxianshan mountain - Biao Zhu; Binbin Lin; Bing Liu; Hengyi Liu (Journal of Atmospheric and Solar-Terrestrial Physics, 2025)

Triptophenolide aggravates triptolide-induced liver injury through disrupting the biological function of intestine - Binbin Zhang; Qiuxia Lin; Manyun Dai; Zhanxuan Wu; Liqiong Chen; Fei Li (Toxicology and Applied Pharmacology, 2025)

Proteoglycans and glycosaminoglycans: critical regulators in angiogenesis, vasculogenesis, and vascularized tissue engineering - Binbin Lin; Tianyu Sun; Yiqi Feng; Hongyu Liu; Lingling Zhang; Buling Wu; Jingyi Wu (Angiogenesis, 2025)

Searching for neutrinoless double-beta decay of 136 Xe with PandaX-4T - Shu Zhang; Zihao Bo; Wei Chen; Xun Chen; Yunhua Chen; Zhaokan Cheng; Xiangyi Cui; Yingjie Fan; Deqing Fang; Zhixing Gao; Lisheng Geng; Karl Giboni; et al. (Science Bulletin, 2025)

Flow fusion characteristics and particle screening effect in Coandă effect hydraulic model - Haoyu Wang; Xianghui Su; Yongwei Ren; Binbin Chen; Zhe Lin; Ling Zhou (Ocean Engineering, 2025)

Apex ambition: Environmental management system certification in Chinese business groups - Shihao Yin; Zhongguo Lin; Binbin Peng; Qiang Ji; Huibin Du (Journal of Environmental Management, 2025)

Integration of volatile and nonvolatile metabolite profiles, and PPO activity reveals the methyl jasmonate protective advantage and metabolite characteristics of Houttuynia cordata during storage - Zengyi Song; Haijiao Lin; Yu Liu; Hongxi Zhang; Binbin Wei; Min Gu (Food Chemistry, 2025)

Gibberellin induces rapid regeneration of juveniles from the Sargassum fusiforme holdfasts - Lin Luo; Dongya Bao; Congquan Gao; Xingda Sheng; Peng Jin; Xu Gao; Zengling Ma; Binbin Chen; Mingjiang Wu (Aquaculture, 2025)

Natural borneol improves cellular uptake of curcumin to enhance its photodynamic bactericidal activity against Escherichia coli ATCC 8739 - Zhenlong Zhou; Ruoxin Chen; Pengzhen Li; Penghui Fan; Lin Ma; Xinyu Cai; Yuchao Hou; Binbin Li; Jianyu Su (Food Microbiology, 2025)

Impact of Carbon and Nitrogen Assimilation in Sargassum fusiforme (Harvey) Setchell due to Marine Heatwave Under Global Warming - Xingda Sheng; Xiaojie Zuo; Lin Luo; Guanfeng Pang; Huawei Zhang; Kit Wayne Chew; Dongshun Fang; Binbin Chen; Mingjiang Wu (Global Change Biology, 2025)
Because of the rising global temperatures, Sargassum fusiforme (Harvey) Setchell, a commercially valuable seaweed, has experienced reduced yield and quality due to high temperatures from marine heatwave events. However, the mechanisms underlying the effects of heatwave stress on S. fusiforme remain unclear. In this study, the mechanisms of heatwave stress on the carbon and nitrogen assimilation processes in S. fusiforme were analyzed. These results indicated that heatwave stress, especially at 30°C for 12 days, significantly increased the levels of hydrogen peroxide (83%), malondialdehyde (84.7%), and relative conductivity (16.5%) in algae, which suggested an increase in algal damage. Morphologically, heatwave stress damaged the thylakoid structure and reduced the photosynthetic efficiency of algae and accumulated NADPH, ATP, and α‐ketoglutarate significantly, resulting in decreased content of mannitol, the photosynthetic product. Additionally, physiological and transcriptomic results revealed that heatwave stress inhibited the rate of nitrate absorption rate and the activities of the most enzymes associated with nitrogen accumulation, while significantly upregulating glutamate dehydrogenase (GDH), suggesting a crucial role for GDH in S. fusiforme 's adaptation to heatwave stress. In terms of amino acid composition, proline and alanine were the most sensitive to heatwave treatment. Moreover, under the natural heatwave environment simulation validation experiment, the algae showed the same physiological performance as under laboratory conditions. The results indicated that marine heatwave events increased oxidative damage in S. fusiforme and inhibited carbon and nitrogen absorption and assimilation, ultimately leading to negative effects on the growth of algae. Thus, in the context of rapid global warming exacerbating marine heatwave events, our study provides valuable insights for high‐temperature‐resistant breeding and ecological management in coastal aquaculture.

Evaluating the impacts of converting grain to vegetable fields on nitrate transport in the deep vadose zone of the North China Plain - Meiying Liu; Leilei Min; Lin Wu; Yucui Zhang; Yongqing Qi; Shiqin Wang; Binbin Liu; Di Geng; Yanjun Shen (Journal of Geographical Sciences, 2025)

Steam-exploded Dictyophora indusiata polysaccharide regulated gut microbiota based on dynamic in vitro stomach-intestine digestion system - Zhikun Zeng; Hangyu Huang; Lin Wang; Yaqing Lin; Binbin Wang; Baodong Zheng; Yi Zhang; Lei Pan (Food Bioscience, 2024)

Effects of temperature and salinity on indoor preservation of in vitro holdfast of Sargassum fusiforme - Lili Xu; Cong Cao; Shuaipeng Tian; Lin Luo; Xiaojie Zuo; Lidong Lin; Mingjiang Wu; Binbin Chen (Aquaculture International, 2024)

Simulation of red mud/phosphogypsum-based artificial soil engineering applications in vegetation restoration and ecological reconstruction - Yong Liu; Lishuai Zhang; Binbin Xue; Li Chen; Guocheng Wang; Jingfu Wang; Hefeng Wan; Xiaohong Lin; Guangxu Zhu (Science of The Total Environment, 2024)

Dynamic response analysis of a fully coupled aerodynamic-hydrodynamic-mooring-anchor floating offshore wind turbine - Dongsheng Qiao; Yichen Zhou; Binbin Xu; Jianmin Qin; Guoqiang Tang; Lin Lu; Jinping Ou (Ocean Engineering, 2024)

The impact of latent policy synergy between cities on air pollution: An empirical analysis from China's 12,764 air policies - Peide Zhang; Binbin Peng; Zhongguo Lin; Huibin Du (Journal of Environmental Management, 2024)

Reducing the overpotential of overall water spitting by micro-pump-like electrode engineering - Tianbiao Zeng; Jie Lin; Biao Wang; Binbin Guo; Yihong Ding; Chang Q Sun (Chemical Engineering Journal, 2024)

Single-atom oxide-decorated AuNPs for universal enhancement in SERS detection of pesticide residues - Qi Zhang; Binbin Chen; Qingbian Ma; Zunlong Fang; Shu Li; Xiaoyu He; Yufeng Wang; Xiaohua Qi; Qian Chen; Ting Cai; Lin Zhang; Mingqiang Zou; et al. (Analytica Chimica Acta, 2024)

Characterization of particle motion of a double-row hydraulic sluicing collector for deep-sea mining - Yongwei Ren; Xianghui Su; Haoyu Wang; Binbin Chen; Lin Zhe; Zuchao Zhu (Ocean Engineering, 2024)

Untargeted metabolomics analysis using UPLC-QTOF/MS and GC–MS to unravel changes in antioxidant activity and compounds of almonds before and after roasting - Xiao Shan; Lin Li; Yu Liu; Ziwei Wang; Binbin Wei; Zhongbo Zhang (Food Research International, 2024)

Observation of Low-Level Jets in the Eastern Tropical Indian Ocean Based on Shipborne Coherent Doppler Lidar - Haiyuan Wang; Lin Liu; Mengqi Fan; Yang Yang; Guang Yang; Yongliang Duan; Baochao Liu; Qinglei Su; Binbin Zhang; Fengjun Wang; Xuliang Shi; Qiuchi Li; et al. (Journal of Ocean University of China, 2024)

Deciphering spatial-temporal dynamics of flood exposure in the United States, - Joynal Abedin; Lei Zou; Mingzheng Yang; Robert Rohli; Debayan Mandal; Yi Qiang; Humaira Akter; Bing Zhou; Binbin Lin; Heng Cai (Sustainable Cities and Society, 2024)

Unveiling community adaptations to extreme heat events using mobile phone location data - Hao Tian; Heng Cai; Leiqiu Hu; Yi Qiang; Bing Zhou; Mingzheng Yang; Binbin Lin (Journal of Environmental Management, 2024)

Does digital economy keep enterprises out of green innovation trouble? evidence from “double carbon” goal - Huiquan Li; Jingdong Li; Binbin Qin; Xiaoshuang Sun; Qingning Lin (Environmental Science and Pollution Research, 2024)

Stabilized Hf-doped Ti/Sb-SnO2 electrode for efficient degradation of tetracycline - Danni Li; Xin Guo; Xiang Shao; Anhui Zhou; Lin Zhu; Yuting Zhang; Binbin Li; Yan Du; Limei Cao; Ji Yang (Environmental Science and Pollution Research, 2024)

The impact of tectonic inversion on diagenesis and reservoir quality of the Oligocene fluvial sandstones: The upper Huagang formation, Xihu Depression, East China Sea Shelf Basin - Jianli Lin; Chunmei Dong; Chengyan Lin; Dongping Duan; Pengjie Ma; Ziru Zhao; Binbin Liu; Xianguo Zhang; Xin Huang (Marine and Petroleum Geology, 2024)

Electro-oxidation of ammonia nitrogen using W, Ti-doped IrO2 DSA as a treatment method for mariculture and livestock wastewater - Yiheng Zhang; Binbin Li; Wenjing Zhang; Xin Guo; Lin Zhu; Limei Cao; Ji Yang (Environmental Science and Pollution Research, 2024)

Symbiotic virus-bacteria interactions in biological treatment of coking wastewater manipulating bacterial physiological activities - Shuang Zhu; Zhijie Tan; Ziyu Guo; Huijian Zheng; Baoshan Zhang; Zhi Qin; Junting Xie; Yuexia Lin; Binbin Sheng; Guanglei Qiu; Sergei Preis; Chaohai Wei (Water Research, 2024)

Effects of nozzle angles of a double-row jet collector on harvesting performance - Xianghui Su; Binbin Chen; Hao Yang; Yongwei Ren; Haoyu Wang; Renyong Lin (Ocean Engineering, 2024)

Observations of anomalously strong mode-2 internal solitary waves in the central Andaman sea by a mooring system - Zijian Cui; Weifang Jin; Tao Ding; Chujin Liang; Feilong Lin; Beifeng Zhou; Binbin Guo; Qianyong Liang (Deep Sea Research Part I: Oceanographic Research Papers, 2024)

Three-phase Enriched Environment Improves Post-stroke Gait Dysfunction via Facilitating Neuronal Plasticity in the Bilateral Sensorimotor Cortex: A Multimodal MRI/PET Analysis in Rats - Yun Lu; Ziyue Lin; Mingcong Li; Yuming Zhuang; Binbin Nie; Jianfeng Lei; Yuanyuan Zhao; Hui Zhao (Neuroscience Bulletin, 2024)

Influence of Pore Structure Characteristics of Low Permeability Coal on Gas Nonlinear Seepage - Min Yan; Fan Yang; Binbin Zhang; Haifei Lin; Shugang Li (Natural Resources Research, 2024)

A novel brain targeting MnOx-based MI-3 nanoplatform for immunogenic cell death initiated high-efficiency antitumor immunity against orthotopic glioblastoma - Xuejie Wang; Zhanfeng Wang; Ping'an Ma; Sainan Liu; Meifang Wang; Ping Chen; Binbin Ding; Jun Lin (Chemical Engineering Journal, 2024)

Asexual proliferative seedling technology for Sargassum fusiforme constructed using tissue culture method - Lina Guo; Guanfeng Pang; Lin Luo; Congquan Gao; Binbin Chen; Zengling Ma (Frontiers in Marine Science, 2024)
The traditional method of sexual reproduction in Sargassum fusiforme can lead to difficulties in maintaining the stable inheritance of superior traits. However, technology for asexual proliferation of seedlings in seaweed tissue culture is not well-developed. Therefore, we established a tissue culture method to study, the effects of different parts of S. fusiforme , uniconazole (UIZ) concentrations, and culture methods on the regeneration of tissue-derived juveniles of S. fusiforme . The results showed that the optimal culture conditions were solid medium with modified Provassoli’s enriched seawater containing 3 μM UIZ for at least 17 days followed by transfer to liquid medium to induce rapid cell proliferation. These optimal conditions resulted in a callus-like/adventitious bud induction rate of 100%, callus-like/adventitious bud number per explant of 27.43 ± 4.57, and relative growth rate of 3.05 ± 0.27. The best plant parts for tissue culture were the filamentous holdfasts followed by the stem tip. In addition, UIZ treatment increased photosynthesis, resulting in soluble sugar and soluble protein contents of 30.47 mg·g -1 and 1.39 mg·g -1 of in the regenerated juveniles. Based on our results, S. fusiforme can be cultured using a tissue culture technique in which UIZ is added to a solid medium, followed by culture in liquid medium for proliferation. Sargassum fusiforme juveniles obtained using this technique can be cultured continuously until the next culture season and grow normally, providing a technical reference for indoor preservation and expansion of algal species.

Migration characteristics of nodules at the critical position of a Coandă effect harvesting model - Xianghui Su; Haoyu Wang; Binbin Chen; Yongwei Ren; Zuchao Zhu; Yong Zhang; Renyong Lin (Ocean Engineering, 2024)

Iron nanoparticle coating and plasma-activated water cleaning as a biofouling removal method for reverse osmosis membranes suitable for desalination - Angelina Egorova; Binbin Xia; Heema Kumari Nilesh Vyas; Maria Magdalena Armendáriz-Ontiveros; Yi-Chen Lin; Alejandra Garcia-Garcia; David K. Wang; Patrick J. Cullen; Gustavo Fimbres Weihs; Anne Mai-Prochnow (Journal of Water Process Engineering, 2024)

Interface chemistry affected the digestion fate of ketogenic diet based on medium- and long-chain triglycerides - Xue Li; Yang Cheng; Zheng Xu; Xiujun Lin; Bolin Xu; Ziwei Wang; Pan Li; Binbin Nian (Food Research International, 2024)

Effects of temperature and irradiance on the growth of regenerated juveniles from Sargassum fusiforme holdfasts - Li Liang; Lin Luo; Hangjun Wang; Mingjiang Wu; Xiaojie Zuo; Binbin Chen; Zengling Ma (Marine Biology Research, 2024)

Effect of temperature on product properties and synergies during the co-pyrolysis of paper sludge and corn stover - Binbin Tang; Peng Fu; Yadong Guo; Zheng Wang; Jingfa Zhang; Xiaona Lin (Journal of Environmental Chemical Engineering, 2024)

Revealing the formation mechanisms of key flavors in fermented broad bean paste - Yue Xiang; Binbin Zhou; Chunyan Jiang; Zhirui Tang; Ping Liu; Wenwu Ding; Hongbin Lin; Jie Tang (Food Research International, 2024)

Improvement of the efficiency for rim-driven thrusters through acceleration of gap flow - Boao Cai; Qing Xu; Binbin Tian; Liaoyuan Qiu; Wei Chai; Jianzhang Qi; Lin He (Ocean Engineering, 2024)

Temporal and spatial changes of major endogenous phytohormones during the regeneration of juveniles from Sargassum fusiforme holdfasts - Guanfeng Pang; Lin Luo; Lina Guo; Congquan Gao; Xingda Sheng; Zengling Ma; Binbin Chen; Mingjiang Wu (Journal of Applied Phycology, 2023)

Application and evaluation of layering shear method in LADCP data processing - Zijian Cui; Chujin Liang; Binbin Guo; Feilong Lin; Yong Mu (Acta Oceanologica Sinica, 2023)

Highly efficient production of monocyclic aromatics from catalytic co-pyrolysis of biomass and plastic with nitrogen-doped activated carbon catalyst - Xiaona Lin; Xiaoyun Chen; Peng Fu; Binbin Tang; Dongmei Bi (Chemical Engineering Journal, 2023)

Physiological responses of Sargassum fusiforme seedlings to high-temperature stress - Xiaojie Zuo; Lili Xu; Lin Luo; Yangyi Zeng; Zengling Ma; Mingjiang Wu; Binbin Chen (Regional Studies in Marine Science, 2023)

Comparative antioxidant activity and untargeted metabolomic analyses of cherry extracts of two Chinese cherry species based on UPLC-QTOF/MS and machine learning algorithms - Ziwei Wang; Lin Zhou; Wenqian Hao; Yu Liu; Xia Xiao; Xiao Shan; Chenning Zhang; Binbin Wei (Food Research International, 2023)

Ultrafast self-assembled supramolecular nanoparticles for enhanced chemodynamic therapy and ferroptosis through lactic acid metabolism regulation - Qi Meng; Jia Tan; Weifang Tong; Changxiao Chen; Zhendong Liu; Sainan Liu; Meifang Wang; Ziyong Cheng; Binbin Ding; Ping'an Ma; Jun Lin (Chemical Engineering Journal, 2023)

Profiling of single-vesicle surface proteins via droplet digital immuno-PCR for multi-subpopulation extracellular vesicles counting towards cancer diagnostics - Chunchen Liu; Huixian Lin; Jingyun Guo; Chao Yang; Jing Chen; Weilun Pan; Binbin Cui; Junjie Feng; Ye Zhang; Bo Li; Shuhuai Yao; Lei Zheng (Chemical Engineering Journal, 2023)

The characteristics and origin of chlorite coats in the Oligocene gas sandstone reservoirs of the Upper Huagang Formation, Xihu Depression, East China Sea Shelf Basin - Jianli Lin; Chengyan Lin; Pengjie Ma; Chunmei Dong; Binbin Liu; Xin Huang; Xianguo Zhang; Xiaohan Zhao (Sedimentary Geology, 2023)

Oxidative Stress in Diabetic Peripheral Neuropathy: Pathway and Mechanism-Based Treatment - Qingxia Lin; Kezheng Li; Yinuo Chen; Jiali Xie; Chunxue Wu; Can Cui; Binbin Deng (Molecular Neurobiology, 2023)

Taxonomic and Morpho-Functional Photosynthetic Patterns of 18 Intertidal Macroalgal Species in the Guangdong–Hong Kong–Macao Greater Bay Area, China - Quan He; Linqing Liu; Yujie Qin; Qiang Lin; Guangyan Ni; Binbin Chen; Zengling Ma; Dinghui Zou; Gang Li (Journal of Marine Science and Engineering, 2023)
Macroalgae provide food for microbial, meio- and macro-faunal communities in coastal ecosystems, thus mediating nutrient dynamics and functions in these ecosystems. Because of this vital role, it is important to clarify physiological information about macroalgae as it reflects their growth potential in the field. In this study, we examined the biomass, pigment content, and photosynthetic O2 evolution rate versus irradiance curves of 18 macroalgal species from the intertidal zone of the Guangdong–Hong Kong–Macao Greater Bay Area, China, and investigated their photosynthetic patterns in relation to phyla characteristics, morphology, and growth locations. The results showed that green algae had the highest maximum photosynthetic O2 evolution rate (Pmax), light utilization efficiency (α), and dark respiration (Rd) among the three macroalgal phyla; the sheet-like macroalgal species had the highest Pmax, α, and Rd among the four morphological categories. The macroalgal species in the upper intertidal zone showed higher Pmax and α and lower saturation irradiance (EK) and compensation irradiance (EC) than those species in the lower intertidal location. The PCA results showed that the biomass of sheet-like macroalgal species was positively correlated with factor PC1 (50.34%), and that of finely branched species was negatively correlated with factor PC2 (25.17%). In addition, our results indicate that the light absorption and utilization capabilities of macroalgae could determine whether they could dominate the intertidal zone and that their photosynthetic characteristics could be used as a potential indicator of their biomass distribution in the Greater Bay Area.

Peroxymonosulfate and peroxydisulfate activation by fish scales biochar for antibiotics removal: Synergism of N, P-codoped biochar - Qingyun He; Chenhui Zhao; Lin Tang; Zhifeng Liu; Binbin Shao; Qinghua Liang; Ting Wu; Yuan Pan; Jiajia Wang; Yang Liu; Shehua Tong; Tianjue Hu (Chemosphere, 2023)

Novel covalent organic frameworks based electrospun composite nanofiber membranes as pipette-tip strong anion exchange sorbent for determination of inorganic arsenic in rice - Binbin Kang; Haoliang Liu; Guoying Chen; Hetong Lin; Shaojun Chen; Tuanwei Chen (Food Chemistry, 2023)

Construction of ZnIn2S4/MOF-525 heterojunction system to enhance photocatalytic degradation of tetracycline - Xiansheng Zhang; Zhifeng Liu; Binbin Shao; Ting Wu; Yuan Pan; Songhao Luo; Miao He; Lin Ge; Jingwen Sun; Chunyun Cheng; Jian Huang (Environmental Science and Pollution Research, 2023)

Co-hydrothermal carbonization of polyvinyl chloride and lignocellulose biomasses for chlorine and inorganics removal - Jing Zhang; Yuhan Chen; Xu Xia; Binbin Fu; Chuanjin Lin; Guangchao Jia; Xin Cui; Fang Liu; Peitao Zhao; Yimin Li (Waste Management, 2023)

Construction of a novel S-scheme heterojunction piezoelectric photocatalyst V-BiOIO3/FTCN and immobilization with floatability for tetracycline degradation - Ting Wu; Qinghua Liang; Lin Tang; Jialin Tang; Jiajia Wang; Binbin Shao; Shanxi Gong; Qingyun He; Yuan Pan; Zhifeng Liu (Journal of Hazardous Materials, 2023)

Effects of exogenous hormones on the regeneration of juveniles from Sargassum fusiforme holdfasts - Lin Luo; Xiaojie Zuo; Lina Guo; Guanfeng Pang; Zengling Ma; Mingjiang Wu; Binbin Chen (Frontiers in Marine Science, 2023)
During the cultivation of Sargassum fusiforme , sexual reproduction of superior strains can hinder the stable inheritance of their desirable traits and reduce their economic benefits. However, vegetative reproduction of S. fusiforme holdfasts has high potential for subculture. In this study, we investigated the effects of different concentrations of α-naphthaleneacetic acid (NAA), gibberellin (GA 3 ), and 6-benzyladenine (BAP) on the growth and regeneration of S. fusiforme holdfasts. Exogenous application of 1.5, 2 mg·L -1 NAA, 1.5 mg·L -1 GA 3 or 2, 3 mg·L -1 BAP significantly promoted photosynthetic activity and the absorption and utilization of nitrate nitrogen in S. fusiforme holdfasts, thus improving the relative growth rate (RGR) and regeneration rate (RR) and shortening the time for the regeneration of juveniles from S. fusiforme holdfasts to around the 6th day. Among these, the RGR and RR at the end of the culture period with 1.5 mg·L -1 of NAA increased by 118.9% and 67.4%, respectively, compared with those of the control group. However, treatment with 1.5 mg·L -1 GA 3 increased the RR of S. fusiforme holdfasts by 58.8% compared with that of the control group. Under BAP treatment at 3 mg·L -1 , the RR of S. fusiforme holdfasts increased by 23.4% compared with that of the control group; its promoting effect was thus weaker than that of NAA and GA 3 . When the concentration of GA 3 or BAP was too high (3 mg·L -1 ; 5 mg·L -1 ), the RR of the holdfasts decreased by 46.5% and 42.8%, respectively compared with that of the control group. Therefore, exogenous application of NAA at 1.5 mg·L -1 , GA 3 at 1.5 mg·L -1 , and BAP at 3 mg·L -1 can be used to induce regeneration of S. fusiforme holdfasts, shorten the culture time of regenerated seedlings, and obtain more regenerative seedlings, thereby improving economic efficiency.

Application of carbon aerogel-based materials in persulfate activation for water treatment: A review - Binbin Shao; Yuantao Xu; Zhifeng Liu; Ting Wu; Yuan Pan; Xiansheng Zhang; Miao He; Lin Ge; Yue Lu; Yang Liu; Weimin Zeng; Lin Tang (Journal of Cleaner Production, 2023)

Strict rule-based automatic training data extraction using Mobile laser scanning in urban area - Zhenyu Ma; Sander Oude Elberink; Yaping Lin; Panpan Xu; Binbin Xiang; Barbara Koch; Holger Weinacker (ISPRS Journal of Photogrammetry and Remote Sensing, 2023)

Disinfection byproducts formation from emerging organic micropollutants during chlorine-based disinfection processes - Binbin Shao; Leyuan Shen; Zhifeng Liu; Lin Tang; Xiaofei Tan; Dongbo Wang; Weimin Zeng; Ting Wu; Yuan Pan; Xiansheng Zhang; Lin Ge; Miao He (Chemical Engineering Journal, 2023)

Differentiation and Temperature Adaptation of Pampus Echinogaster Based on Genome-Wide SNPs - Yuan Li; Fangrui Lou; Shigang Liu; Hai Li; Jiali Xiang; Binbin Shan; Longshan Lin; Xuan Zhuang (Frontiers in Marine Science, 2022)
Climate change and overfishing have led to the degradation of the quality and stock of Pampus echinogaster. Exploring the genetic structure and local adaptive evolutionary mechanisms of P. echinogaster is crucial for the management of this species. This population genomic study of nine geographical populations of P. echinogaster in China was conducted by specific-locus amplified fragment sequencing (SLAF-seq). A total of 935,215 SLAF tags were obtained, and the average sequencing depth of the SLAF tags was 20.80×. After filtering, a total of 46,187 high-consistency genome-wide single nucleotide polymorphisms (SNPs) were detected. Based on all SNPs, the population size of the nine P. echinogaster geographical populations was large. The Shantou population had the lowest genetic diversity, and the Tianjin population had the highest. Moreover, the population genetic structure based on all SNPs revealed significant gene exchange and no significant genetic differentiation among the nine P. echinogaster geographical populations, probably because of the population expansion after the last glacial period, the lack of balance between migration and genetic drift, and the long-distance diffusion of eggs and larvae. We suspect that variation of material metabolism, ion transfer, breeding, stress response, and inflammatory reactions-related genes were critical for adaptation to spatially heterogeneous temperature selection in natural P. echinogaster populations.

Research on gas diffusion of natural gas leakage based on Gaussian plume model - Binbin Wang; Liqiong Chen; Wanxin Lin; Dongrong Wu; Yingchao Fang; Zhao Li (Arabian Journal of Geosciences, 2022)

Harmful algal bloom-forming dinoflagellate Prorocentrum donghaiense inhibits the growth and photosynthesis of seaweed Sargassum fusiformis embryos - Caixia Wang; Min Wang; Binbin Chen; Wenli Qin; Lidong Lin; Chuanjun Dai; Hengguo Yu; Renhui Li; Min Zhao; Zengling Ma (Journal of Oceanology and Limnology, 2021)

Estimation of the appropriate sampling interval for rock joints roughness using laser scanning - Yunfeng Ge; Zishan Lin; Huiming Tang; Binbin Zhao (Bulletin of Engineering Geology and the Environment, 2021)

Investigation of the effects of nonstationary features on rock joint roughness using the laser scanning technique - Yunfeng Ge; Zishan Lin; Huiming Tang; Binbin Zhao; Hongzhi Chen; Zhiguo Xie; Bin Du (Bulletin of Engineering Geology and the Environment, 2020)

Synergy of orographic drag parameterization and high resolution greatly reduces biases of WRF-simulated precipitation in central Himalaya - Yan Wang; Kun Yang; Xu Zhou; Deliang Chen; Hui Lu; Lin Ouyang; Yingying Chen; Lazhu; Binbin Wang (Climate Dynamics, 2020)

Role of the prefrontal lobe in young normotensives with a family history of hypertension and hypertensives - Xiaoni Wang; Fadong Zhao; Saisai Yan; Xinzhu Zhang; Lin Xie; Binbin Liu; Xiaohui Di; Yi Li; Jianbao Zhang (Pflügers Archiv - European Journal of Physiology, 2019)

A rapid loess mudflow triggered by the check dam failure in a bulldoze mountain area, Lanzhou, China - Fanyu Zhang; Binbin Yan; Xiaoming Feng; Hengxing Lan; Chao Kang; Xishan Lin; Xinghua Zhu; Wenguo Ma (Landslides, 2019)

Relationship between warfarin dosage and international normalized ratio: a dose–response analysis and evaluation based on multicenter data - Ling Xue; Yuzhen Zhang; Cheng Xie; Ling Zhou; Linsheng Liu; Haiyan Zhang; Lianhong Xu; Hongtao Song; Meiqin Lin; Hanfan Qiu; Junrong Zhu; Yubing Zhu; et al. (European Journal of Clinical Pharmacology, 2019)

Carbon and nitrogen accumulation and interspecific competition in two algae species, Pyropia haitanensis and Ulva lactuca, under ocean acidification conditions - Binbin Chen; Lidong Lin; Zengling Ma; Tiantian Zhang; Weizhou Chen; Dinghui Zou (Aquaculture International, 2019)

Intramuscular Delivery of scAAV9-hIGF1 Prolongs Survival in the hSOD1G93A ALS Mouse Model via Upregulation of D-Amino Acid Oxidase - HuiQian Lin; HaoJie Hu; WeiSong Duan; YaLing Liu; GuoJun Tan; ZhongYao Li; YaKun Liu; BinBin Deng; XueQin Song; Wan Wang; Di Wen; Ying Wang; et al. (Molecular Neurobiology, 2018)

A nanocomposite film fabricated with simultaneously extracted protein-polysaccharide from a marine alga and TiO2nanoparticles - Qingyan He; Yan Huang; Binbin Lin; Shaoyun Wang (Journal of Applied Phycology, 2017)

Air temperature estimation with MODIS data over the Northern Tibetan Plateau - Fangfang Huang; Weiqiang Ma; Binbin Wang; Zeyong Hu; Yaoming Ma; Genhou Sun; Zhipeng Xie; Yun Lin (Advances in Atmospheric Sciences, 2017)

Proteomic analysis of Mortierella isabellina M6-22 during cold stress - Binbin Hu; Minzhou Luo; Xiuling Ji; Lianbing Lin; Yunlin Wei; Qi Zhang (Archives of Microbiology, 2016)

Protective effect of myokine IL-15 against H2O2-mediated oxidative stress in skeletal muscle cells - Fengna Li; Yinghui Li; Yulong Tang; Binbin Lin; Xiangfeng Kong; Oso Abimbola Oladele; Yulong Yin (Molecular Biology Reports, 2014)

Myokine IL-15 regulates the crosstalk of co-cultured porcine skeletal muscle satellite cells and preadipocytes - Yinghui Li; Fengna Li; Binbin Lin; Xiangfeng Kong; Yulong Tang; Yulong Yin (Molecular Biology Reports, 2014)

Polymorphisms in arachidonic acid metabolism-related genes and the risk and prognosis of colorectal cancer - Shuying Li; Xiaojuan Zhao; Zhiwei Wu; Ye Li; Lin Zhu; Binbin Cui; Xinshu Dong; Suli Tian; Fulan Hu; Yashuang Zhao (Familial Cancer, 2013)

Small fluctuations in the recovery of fusaria across consecutive sampling intervals with unmanned aircraft 100 m above ground level - Binbin Lin; Amir Bozorgmagham; Shane D. Ross; David G. Schmale III (Aerobiologia, 2013)

Erratum to: Association between gout and polymorphisms in GCKR in male Han Chinese - Jing Wang; Shiguo Liu; Binbin Wang; Zhimin Miao; Lin Han; Nan Chu; Kun Zhang; Dongmei Meng; Changgui Li; Xu Ma (Human Genetics, 2012)

Association between gout and polymorphisms in GCKR in male Han Chinese - Jing Wang; Shiguo Liu; Binbin Wang; Zhimin Miao; Lin Han; Nan Chu; Kun Zhang; Dongmei Meng; Changgui Li; Xu Ma (Human Genetics, 2012)

Genetic analysis of ABCG2 gene C421A polymorphism with gout disease in Chinese Han male population - Binbin Wang; Zhimin Miao; Shiguo Liu; Jing Wang; Shiyi Zhou; Lin Han; Dongmei Meng; Yunlong Wang; Changgui Li; Xu Ma (Human Genetics, 2010)

Cloning, expression and reactivating characterization of glycerol dehydratase reactivation factor from Klebsiella pneumoniae XJPD-Li - Gen Lin Zhang; Xiao Lin Xu; Chun Li; BinBin Ma (World Journal of Microbiology and Biotechnology, 2009)